PERUBAHAN NILAI BUDAYA MASYARAKAT INDONESIA DI ERA DIGITAL - Nur Hikma; Irwansyah; Said Hanafi; Muhammad Nurhidayat (STKIP Subang, 2026)
This The development of digital technology has brought significant changes to the cultural values of Indonesian society. Social media and the internet have not only transformed communication patterns but also influenced cultural identity, social relations, and the way younger generations interpret local and global cultures. This study aims to examine the transformation of cultural values in Indonesian society in the digital era, including changes in social values in digital interactions, the role of social media in shaping cultural values, shifts in cultural identity, their impact on younger generations, as well as opportunities and challenges in cultural preservation. This research employed a qualitative approach using a library research method. Data were collected from various scientific sources such as journals, books, and research reports relevant to the study topic. Data analysis was conducted using qualitative content analysis by systematically classifying and interpreting the findings. The results indicate that the digital era has shifted social values from deep and emotional relationships toward more flexible and network-based interactions. Social media also contributes to the formation of hybrid cultural identities through the integration of local and global cultural elements. On the other hand, digital technology provides significant opportunities for cultural preservation through the digitization and dissemination of local cultural content. Therefore, strengthening culture-based digital literacy and encouraging the active role of younger generations are essential to maintaining the sustainability of local culture amid the flow of digital globalization.